Influence of Different Composites and Polishing Techniques on Periodontal Tissues near Noncarious Cervical Lesions: A Controlled, Randomized, Blinded Clinical Trial - Teixeira, Nancielli; Webber, Mariana Benedetti Ferreira; Nassar, Carlos Augusto; Camilotti, Veridiana; Mendonça, Marcio José; Sinhoreti, Mario Alexandre Coelho (European Journal of Dentistry, 2019)
Objectives This study evaluated the long-term effect on gingival tissues near noncarious cervical lesions after restoration with different composites in association with two different polishing techniques.Materials and Methods This study was conducted on 60 patients as a randomized, split-mouth, single-blind clinical trial and divided into four groups (n = 15) and restored using different composites (Tetric N-Ceram nanohibride or Z350 XT nanoparticles) and polishing materials (Astropol or Sof-Lex). The periodontal parameters analyzed were Silness–Löe plaque index; Silness–Löe gingival index; probing depth, clinical insertion level; and bleeding on probing. Periodontal analysis was performed before scaling and root planing at 30, 60, 120, and 180 days after restoration.Statistical Analysis The data submitted to the Friedman’s test were employed for comparison between groups (p < 0.05).Results Statistically significant differences between Z350/Astropol and other groups were observed for visible plaque and probing depth. Gingival index Tetric/Sof-Lex, the time factor did not influence the results. All experiment groups exhibited statistically significant differences in the clinical level of insertion when the follow-up time was considered. Percentage of bleeding on probing, in which there was a difference only with regard to group Tetric/Sof-Lex when the time factor was considered.Conclusion The evaluated composites and polishing techniques did not exhibit differences in performance in the periodontal parameters analyzed at the end of 6 months of evaluation.
Keywords: inflammation; composite resins; dental polishing; noncarious cervical lesion